TGF‐β & BMP Receptors Endoglin and ALK1: Overview of their Functional Role and Status as Antiangiogenic Targets. (February 2014) - Jonker, Leon
Abstract The formation of new blood vessels from existing vasculature, angiogenesis, is facilitated through a host of different signaling processes. Members of the TGF‐β superfamily, TGF‐β1, TGF‐β3, and BMP9, are key propagators of both inhibition and initiation of angiogenesis. HHT, characterized by AVM and capillary bed defects, is caused by germline mutations in the ENG and ACVRL1/ALK1 genes, respectively. Clinical symptoms include epistaxis and GI hemorrhage. The membranous receptors endoglin and ALK1 activate proliferation and migration of endothelial cells during the angiogenic process via the downstream intracellular SMAD signaling pathway. Endothelial cell senescence or activation is dependent on the type of cytokine, ligand concentration, cell–cell interaction, and a multitude of other signaling molecules. Endoglin and ALK1 receptor levels in tumor vasculature correlate inversely with prognosis in humans, whereas in mice, endoglin deficiency decelerates tumor progression. Therefore, endoglin and ALK1 have been identified as potential therapeutic targets for antibody treatment in various cancers. Early phase clinical trials in humans are currently underway to evaluate the efficacy and safety of biological therapy targeting endoglin/ALK1‐mediated cells signaling.